Fear, overconfidence, and fundamental uncertainty shocks. Issue 9 (21st May 2021) - Ambrocio, Gene
ABSTRACT: I study the effects of expected and realized uncertainty on Euro area macroeconomic conditions. I use a range of expected and realized uncertainty measures including those based on survey forecasts and find that the effects of expected uncertainty vanish once realized uncertainty is accounted for when using financial or news media-based measures. On the other hand, shocks to a survey-based measure of expected uncertainty do appear to have dampening effects.